Labor protection of nannies - Popović, Aleksandra T (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Labor protection of nannies Abstract: Nannies work is specific and highly sensitive, considering that it includes keeping and caring for children according to their age, taking care of physical and psychological health, safety, nutrition and hygiene, respecting their rights, personal integrity and dignity. The nannies job description includes taking care of children’s daily rest, play, entertainment, school duties, free activities, and may also include taking children to and from school, on recreational and additional educational activities, with continuous monitoring and improvement of their physical, emotional, intellectual and social development. Education and upbringing of children is also an important segment of the nannies activity, as well as teaching life and social skills, according to the parents instructions. Bearing in mind the peculiarities and nature of the job of a nanny, there is a need to more precisely determine their labor protection in the law of the Republic of Serbia. By creating a more precise legislative framework for the performance of nannies, multiple benefits would be achieved: nannies would receive a higher degree of labor law protection, and parents and children would have greater security, because it would be possible for children to be cared for by professionally qualified persons in an adequately arranged space, in the prescribed manner under the continuous supervision and control of competent institutions over their work.